PENGARUH PEMBERIAN PAKAN HIJAUAN PADA PERTAMBAHAN BOBOT BADAN HARIAN SAPI BALI JANTAN SELAMA SATU MINGGU - Anderson Maku Djawa; Atqya Rahman Hadi; I Putu Alga Aridana; Nurul Yakin; Ahmad Hammas Zahfi (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Forage is the primary source of fiber and nutrients in cattle farming, so increasing body weight is crucial in feed management. This study aims to determine the effect of forage feeding on the daily body weight gain of male Bali cattle for one week. This study was conducted at SIMANTRI SELANBAWAK KELOD, SELANBAWAK, MARGA, TABANAN, with the owner's name I WAYAN KANTOR. Optimal feeding can result in significant body weight gain (PBH), ranging from 0.64 to more than 3 kg/head/week, depending on the type of cattle and feed quality. Without sufficient supplemental feed, PBBH may only reach 0.3-1 kg/head/week. The results of the study showed that the cattle initially weighed 259.21 kg, but with regular feeding for one week, the cattle achieved a final body weight of 262.44 kg in one week. Therefore, the cattle's body weight gain for one week was 3.23 kg. This study shows that green fodder can support cattle growth in the short term.